The Role of Parmedics in Addressing the Health Insecurity of Older Adults in Humanitarian Emergencies: A Systematic Review - Megan De Silva; Lloyd Denzil Christopher; Aidan Peters; Navindhra Naidoo (Health Security, 2026)
Older adults are disproportionately exposed to greater risk of harm and adverse outcomes in humanitarian emergencies. This systematic review explores and evaluates contemporary evidence on the role of paramedics in responding to humanitarian emergencies, with a specific focus on their ability to reduce the vulnerability potential for older adults. A systematic review of the literature was undertaken using Joanna Briggs Institute evidence summary and PRISMA guidelines. From an initial yield of 4,440 results, 16 sources of evidence met the criteria for inclusion and data extraction. Predominantly North American, the literature confirmed that older adults experience disproportionate and complex vulnerability in humanitarian emergencies. As frontline healthcare workers, paramedics are uniquely positioned to respond to community and individual vulnerability before, during, and after emergency exposure, but they experience significant impediments to optimizing practice. There is an unmet professional need to improve paramedic’s capacity to address older adults’ vulnerabilities and to enhance their rights to healthcare, personal protection, and health and social security. This review provides key recommendations for reconceptualizing the duty of care and improving the capacity of paramedics to respond to the vulnerabilities of older adults manifested by humanitarian emergencies.